2014
DOI: 10.1002/ange.201400793
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylierungen von Alkenen mit CO‐Alternativen

Abstract: Alkencarbonylierungen sind wichtige Prozesse für die Produktion von Groß‐ und Feinchemikalien. Heutzutage nutzen alle industriellen Carbonylierungsprozesse das hochtoxische und brennbare Gas Kohlenmonoxid, dessen Eigenschaften einen breiten Einsatz von Carbonylierungen in Industrie und Wissenschaft aber erschweren. Daher ist die Durchführung von Carbonylierungen ohne Verwendung von CO wünschenswert, auch unter den Gesichtspunkten der nachhaltigen Chemie. Obwohl über Alternativen zu Kohlenmonoxid schon seit 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(4 citation statements)
references
References 90 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…With the exception of carbon monoxide, a variety of organic precursors, such as silacarboxylic acid, oxirane, acid chlorides, N ‐formylsaccharin, formic acid, and carbon dioxide have also been used . For instance, Jun's group reported the use of oxiranes as CO source for the Pd/C‐catalyzed carbonylative esterification of aryl bromides with alcohols in the presence of NaF in 1,4‐dioxane at 150 °C [Eq.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…With the exception of carbon monoxide, a variety of organic precursors, such as silacarboxylic acid, oxirane, acid chlorides, N ‐formylsaccharin, formic acid, and carbon dioxide have also been used . For instance, Jun's group reported the use of oxiranes as CO source for the Pd/C‐catalyzed carbonylative esterification of aryl bromides with alcohols in the presence of NaF in 1,4‐dioxane at 150 °C [Eq.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…Although the yield decreased, no free radical capture species were detected by GC-MS. Then, by replacing CO 2 with CO under our standard conditions, the product 3a was obtained in 54% yield, which suggested that CO might be intermediate for the transformation (Scheme , eq 5). In addition, reduction of CO 2 by PhSiH 3 is likely to proceed through formation of silyl formates {HC­(O)­O–SiR 3 }, which would readily release CO under heating conditions . Indeed, we detected the formation of CO and silyl formate by GC and NMR, respectively (Scheme , eq 6 and Figures S1–S3).…”
Section: Results and Disscussionmentioning
confidence: 99%
“…[2] Carbonylation reactions have been the focus of extensive research in organic syntheses and industrial processes employing CO as the C1 source. [4] The typical known CO surrogate compounds include methanol, [5] 1,3-dioxolane, [6] formaldehyde, [7] paraformaldehyde, [8] silacarboxylic acids, [9] formic acid and its derivatives, [10] acyl chloride derivatives, [11] carbon dioxide, [12] metal carbonyls, [13] and N-formylsaccharin (NFS). Hence, carbonylation methodology conducted without the use of CO would be a reliable and accessible choice for the further advancement of sustainable chemistry.…”
mentioning
confidence: 99%
“…Considerable efforts have been focused on the development of CO surrogates for carbonylation reactions. [4] The typical known CO surrogate compounds include methanol, [5] 1,3-dioxolane, [6] formaldehyde, [7] paraformaldehyde, [8] silacarboxylic acids, [9] formic acid and its derivatives, [10] acyl chloride derivatives, [11] carbon dioxide, [12] metal carbonyls, [13] and N-formylsaccharin (NFS). [14] These reagents offer CO in situ upon heating or metal catalysis or treatment with acid or base to avoid handling the gas; some of them even can be recycled after release of CO. For instance, NFS, working as an easily accessible and highly reactive crystalline CO surrogate, can be easily synthesized from saccharin and also can be reused.…”
mentioning
confidence: 99%